2019
DOI: 10.1245/s10434-019-08090-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Health-Related Quality of Life of Video-Assisted Thoracoscopic Surgery for Lung Cancer

Abstract: Background. Video-assisted thoracoscopic surgery (VATS) approaches are increasingly used in lung cancer surgery, but little is known about their impact on patients' health-related quality of life (HRQL). This prospective study measured recovery and HRQL in the year after VATS for non-small cell lung cancer (NSCLC) and explored the feasibility of HRQL data collection in patients undergoing VATS or open lung resection. Patients and Methods. Consecutive patients referred for surgical assessment (VATS or open surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…In the early stages of these tumors, surgical resection is the primary treatment modality, and the intervention associated with better long-term prognosis [ 2 , 3 ]. However, as a result of surgical resection, there is a significant deterioration in patients’ health-related quality of life (HRQoL) [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of these tumors, surgical resection is the primary treatment modality, and the intervention associated with better long-term prognosis [ 2 , 3 ]. However, as a result of surgical resection, there is a significant deterioration in patients’ health-related quality of life (HRQoL) [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted after lobectomy found that 100% of the patients reported being concerned about the limitations in their physical function and 96% about the levels of fatigue and pain [ 10 ]. Although, in general, HRQoL progressively returns to preoperative levels between 3 to 6 months after LC surgery, it has been shown that domains like physical function, fatigue and dyspnea persist significantly worse than at the preoperative phase for at least 1 to 2 years after surgery [ 4 , 7 , 9 , 11 , 12 , 13 ], even in patients selected for LC resection by video-assisted thoracoscopic surgery (VATS) approaches [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The continuation of chemotherapy may contribute to a lack of improvement in HRQOL after lung resection. In patients who undergo lung resection for cancer, HRQOL does not recover to the preoperative level by 1 year postoperatively [24], [25], and lower HRQOL is associated with continued postoperative chemotherapy [24]. Thus, continued chemotherapy might also decrease HRQOL in patients who undergo surgery for NTM-PD.…”
Section: Discussionmentioning
confidence: 99%
“…Through nutritional supplementation one might be able to optimise recovery after surgery and preventing complications. 23…”
Section: Introductionmentioning
confidence: 99%